West-facing elevation of the Mandaleshwar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
West-facing elevation of the main Mandaleshwar Mahadev Temple is seen here. The mulaprasada (main shrine) of the temple is saptaratha (consisting of seven projections). The intermediate and corner projections of the temple are slender and narrow, devoid of any sculptures. Only the central projection has a sculpture inside a niche.